Interest Rate and Foreign Exchange Risk Exposures of Australian Banks: A Note (International Journal of Banking and Finance, 2009)
The abolition of most government controls over the Australian financial system in the 1980s, the advent of a flexible exchange rate regime in 1983 and the globalisation of the financial system in the 1990s have created new opportunities for Australian banks but exposed them to new sources of risk. This study estimates systematic risk exposure of publicly listed Australian banks with respect to market, interest rate and foreign exchange rate using a GARCH-in-Mean model. Not surprisingly, the results suggest that nearly all banks exhibit varying degrees of market risk exposure. However, stock returns of large banks are highly sensitive to interest rate changes, while most small banks are almost immune to both interest and exchange rate changes.